The impact of identifying laryngeal obstruction syndromes on reducing treatment of pediatric asthma: A systematic review. Issue 6 (22nd April 2022) - Zhang, Caseng; Hicks, Matt; Ospina, Maria B.; Martha, Vishnu; Alnouri, Ghiath; Dennett, Liz; Sataloff, Robert; Hicks, Anne
Abstract: Inducible laryngeal obstruction (ILO) in children is underrecognized. This systematic review characterizes the scientific evidence on the impact of pediatric ILO diagnosis and treatment on asthma medication use. This review, registered with PROSPERO (CRD42020209168), utilized database searches in MEDLINE, EMBASE, CINAHL, and Web of Science from inception to October 2020. Both experimental and observational studies on ILO and asthma outcomes in patients ≤18 years were included. Population characteristics (sample size, sex, age, and comorbidities) and study outcomes (medication usage and respiratory symptoms) were extracted. The risk of bias was assessed with the National Toxicology Program's Office of Health Assessment and Risk of Bias Rating Tool. Data are presented narratively due to study heterogeneity. Of 1091 studies, 1076 titles and abstracts were screened after duplicate removal. Screening 31 full texts yielded eight pre–post studies. Patients were an average of 14.1 years old, 15% male, and >90% used asthma medication; 40% reported allergies, 30% gastroesophageal reflux, and 20% anxiety or depression. Most patients received at least one intervention, with 75% showing symptomatic improvement and >75% decreasing or stopping asthma medications. Studies were small with a high risk of selection, confounding, and detection bias. Asthma management was not a primary outcome in any of the studies. Overall, ILO patients were often diagnosed with or treated for asthma before ILO diagnosis. Evidence from individual studies suggests that comorbidities including ILO, gastroesophageal reflux, allergies, and anxiety should be considered in pediatric patients with asthma not responsive to medical therapy. Further research is required to determine the proportion of impacted asthma patients.